The effect of liquid nitrogen exposure on the proliferative phase of Achilles tendon healing in Rattus norvegicus rats - Istan Irmansyah Irsan; Edi Mustamsir; Panji Sananta; Satria Pandu Persada Isma; Dandy Drestanto Adiwignyo; Hudzaifah Al Azmi Manaf; Adytia Andreyta Refa (Medicinski glasnik, 2026)
Aim: Tendon healing involves a crucial proliferative phase, during which fibroblasts and fibrocytes orchestrate collagen deposition. The use of liquid nitrogen (LN) in orthopedic oncology may inadvertently affect adjacent tendon tissues. This study aimed to evaluate the impact of LN exposure on the histological features of tendon healing. Methods: This experimental study employed a randomized post-test-only control group design involving 24 males Rattus norvegicus, randomly divided into four groups: control (no LN exposure) and three treatment groups exposed to LN for 1, 5, and 10 minutes, respectively, following Achilles tendon transection and repair. After a 21-day healing period, histological analysis was performed to assess the counts of fibroblasts, fibrocytes, and collagen content. Statistical analyses included one-way ANOVA, Post-hoc Tukey, and Pearson correlation (p<0.05 was considered significant). Results: LN exposure significantly reduced fibroblast, fibrocyte, and collagen levels compared to controls (p<0.05). The 10-minute group showed the lowest counts. A significant negative correlation was found between LN immersion duration and the number of fibroblasts (r= -0.87), fibrocytes (r= -0.829), and collagen content (r= -0.83) (p<0.05). Conclusion: Liquid nitrogen (LN) impairs tendon healing in a dose-dependent manner, likely due to cryo-induced cell death and disruption of blood flow. This results in an acellular and avascular tendon matrix, hindering the repair process. LN exposure negatively impacts the proliferative phase of tendon healing in rats, suggesting the need for caution in clinical use to prevent damage to surrounding tendinous tissues.
Keywords: Achilles tendon; cryosurgery; fibroblasts; tendon injuries; wound healing